Standing stock of thorny bamboo [Bambusa bambos (L.) Voss] in the homegardens of Thrissur, Kerala - Kumar, B.M.; Sudheesh, K.G.; Rajesh, G. (Journal of Tropical Agriculture, 2006)
Standing stock of rural bamboo in Thrissur district was assessed through a two-stage stratified random scheme in which 330 homegardens in 10 panchayaths (rural) and one peri-urban area were sampled. The total growing stock of thorny bamboo in the homegardens of Thrissur district was estimated as 32,344 clumps or 22,86,305 culms, having a total dry weight of 28,659 Mg. In general, medium and large-sized holdings were having more bamboo clumps. Such gardeners also felled more bamboo and generated higher cash returns compared to the owners of small holdings. Average cash income generation per farmer through bamboo sale during the period from 1999 to 2004 was, however, modest; Rs. 62, 188 and 199 per garden per year respectively for small, medium and large holdings.